ПРОТИЛЕЖНО-ДОПОВНЮВАЛЬНІ ПРАКТИКИ ОСОБИСТІСНОГО ЖИТТЄКОНСТРУЮВАННЯ У СФЕРАХ РОБОТИ ТА ДОЗВІЛЛЯ - Крайчинська, Валентина Анатоліївна (Psychological Prospects Journal, 2014)
Серйозне та несерйозне (легковажне) соціально-психологічні настановлення особистості проаналізовано для досягнення більшої інформаційної визначеності у невизначеному світі. Розкрито соціально-психологічний зміст, різні життєві практики серйозного та несерйозного настановлень. За загальним тоном текстової презентації практик, що визначався як співвідношення лексичних засобів, притаманних «легкому» та «серйозному» настановленню, відповіді опитуваних поділено на чотири групи: переважно легкий, врівноважений, переважно серйозний і тотально серйозний. Перехід між модусами легкого та серйозного супроводжує зміна властивостей простору життєконструювання з погляду його: 1) реальності, зокрема за допомогою практик даності, уможливлення, втілення та плинності; 2) значущості (через практики центрації,  емоційного «забарвлення» та виділення важливих критеріїв); 3) досяжності (через уведення критерію доступності та необхідної стратегії доступу); 4) контролю (через різноманітні практики оперування простором).Ключові слова: серйозне, несерйозне, легковажне, соціально-психологічні настановлення особистості, життєконструювання, життєві практики, невизначеність.Kraіchynska V. A. Counter-additional Aspects of Personal Life Constructing in Professional Activity and Leasure. Serious and light social-psychological attitudes of personality are treated as a psychological mechanism of certainty in indefinite world. Social-psychological content and dynamics of serious and light attitudes is presented. Types of life-practices of these attitudes are revealed. Light and serious and modi of personality vital construction are treated as two different ways to interact with undefined. One of the methods to dynamically organize the vital construction territory – transition from serious to light and vice versa – is treated in details. The transition between the modi of light and serious vital construction is attended by change of vital construction territory characteristics – derealization, de- creasing, decentralization, and deregulation. Main characteristics of territories of light and serious vital construction are: importance, availability, reality, and control. The general tone of the presentation of textual practices, which is defined as the ratio of lexical means inherent «light» and «serious» admonition, the answers of the respon- dents were divided in 4 groups: mostly easy, balanced, most serious and totally serious.Keywords: serious, light, not serious, personality, life-design, vital construction, life-practices, social-psychological attitudes of personality, territory, undefined.Крайчинская В. А. Противоположно-дополняющие практики личностного жизнеконструирования в сферах работы и досуга. Серьезная и несерьезная (легкомысленная) социально-психологические личностные установки анализируются с целью достижения большей информационной определенности в непределенном мире. Раскрыты социально-психологическое содержание, различные жизненные практики серьезной/несерьезной установок личности. Исходя из общего тона текстовой презентации практик, который определялся как соотношение лексических средств, характерных для «легкой» и «серьезной» установок, ответы опрашиваемых распределились на четыре группы: преимущественно легкая, уравновешенная, преимущественно серьезная и тотально серьезная. Переход между двумя модусами сопровождается изменением свойств пространства жизнеконструирования с точки зрения его: 1) реальности (с помощью практик данности, возможного, воплощения и текучести); 2) значимости (благодаря практикам центрации, эмоционального «раскрашивания», выделения главных критериев); 3) доступности (с помощью критерия и стратегий доступа); 4) контроля (с помощью разнообразных практик оперирования пространством).Ключевые слова: серьезное, несерьезное, легкомысленное, социально- психологические личностные установки, жизнеконструирование, жизненные практики, неопределенность.